2003
DOI: 10.1128/iai.71.2.597-604.2003
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum Infection Elicits Both Variant-Specific and Cross-Reactive Antibodies against Variant Surface Antigens

Abstract: Naturally acquired antibodies to Plasmodium falciparum erythrocyte membrane protein-1 (PfEMP-1), the variant surface antigens expressed on the surface of infected erythrocytes, are thought to play a role in protection against P. falciparum malaria. Here, we have studied the development of antibodies to PfEMP-1 in adult malaria patients living in Rourkela, India, an area with a low malaria transmission rate, and prevalence of antibodies to PfEMP-1 in residents of San Dulakudar, India, a village in which P. falc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 26 publications
4
50
0
Order By: Relevance
“…1A). This observation is consistent with the results of numerous studies that have reported enhancements of the levels of IgG antibodies with specificity for the VSA expressed by heterologous parasite isolates in the postinfection period (5,7,12,16,29). Our data thus strongly imply that cross-reactive antibodies are a prominent feature of the profile of anti-VSA responses induced by P. falciparum malaria episodes in young African children with high and perennial levels of exposure to infection.…”
Section: Discussionsupporting
confidence: 81%
“…1A). This observation is consistent with the results of numerous studies that have reported enhancements of the levels of IgG antibodies with specificity for the VSA expressed by heterologous parasite isolates in the postinfection period (5,7,12,16,29). Our data thus strongly imply that cross-reactive antibodies are a prominent feature of the profile of anti-VSA responses induced by P. falciparum malaria episodes in young African children with high and perennial levels of exposure to infection.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, ancient polymorphic segments have been carried forward into existing parasite populations, possibly from a burst of polymorphism that occurred in the common progenitor to these isolates. Small stretches of shared polymorphism have also been observed between lessconserved var genes and potentially contribute to cross-reactive antibody responses (15,108). These findings suggest that recombination of slowly mutating polymorphic segments has an important role in var gene diversification and that recombining genes may be more likely to share antigenic relationship.…”
Section: Var Gene Diversity Recombination Hierarchies and Evolutionmentioning
confidence: 72%
“…Immune responses to this antigen are crucial for the protection against severe disease, though additional surface antigens might be involved in protection (1,5,7,10,23,24). A potential vaccine candidate is the PfEMP1 of the parasite clone FCR3S1.2 studied here, which is able to bind to multiple host receptors (13,40), analyzed extensively in our in vivo sequestration model based on immunocompetent Sprague-Dawley rats.…”
Section: Discussionmentioning
confidence: 99%